The monetary transmission mechanism in the euro area: more evidence from VAR analysis - Gert Peersman; Frank Smets (European Central Bank (ECB), 2001)
This paper applies the identified VAR methodology to synthetic euro area data from 1980 till 1998 to study the macro-economic effects of an unexpected change in monetary policy in the euro area. The focus is on the area-wide monetary transmission. It is shown that the overall macro-economic effects of a monetary policy shock in the euro area are very similar to those estimated for the United States and are surprisingly stable over time. In addition, the paper contains a number of robustness checks with alternative identification schemes and examines how various real and financial variables (such as the GDP or money components) respond to an area-wide monetary policy impulse
Keywords: E52; 330; monetary transmission mechanism; vector autoregressions